The Challenge of Femicide and Violence Against Women in Turkey - Ince Yenilmez, Meltem; Demir, Mehmet Hulusi (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-ansi-language:TR;} --> <!--[endif] --> <!--StartFragment--> Violence against women in Turkey is a tangible manifestation of the way that Turkish men have used force to exercise dominance over Turkish women. It is considered by many in society as natural, cultural and possibly unchanging. Violence is, inarguably, a critical social challenge throughout Turkey and has not improved, even as the world is addressing it more and more. Violence against women is a crime against human rights, which this study attempts to address. The aim of this paper is to discover the reasons for femicide and violence and to determine whether a change in the legal system can ultimately resolve the problem. Indeed, in present-day Turkey it is very difficult to verify the precise levels of violence against women. The paper concludes that unless there is a fundamental change in attitudes towards women, especially on the part of men, violence against women and femicide will continue to be major challenges and will remain to be properly addressed by lawmakers. Furthermore, because attitudes towards women are not good in Turkey, official statistics regarding violence against women are unreliable, making it that much more difficult to implement targeted, effective measures to address violence against women and femicide. <!--EndFragment-->